Projected risks to groundwater‐dependent terrestrial vegetation caused by changing climate and groundwater abstraction in the Central Perth Basin, Western Australia. Issue 22 (24th September 2013) - Barron, Olga; Froend, Ray; Hodgson, Geoff; Ali, Riasat; Dawes, Warrick; Davies, Phil; McFarlane, Don
Abstract The effect of potential climate change on groundwater‐dependent vegetation largely depends on the nature of the climate change (drying or wetting) and the level of current ecosystem dependence on groundwater resources. In south‐western Australia, climate projections suggest a high likelihood of a warmer and drier climate. The paper examines the potential environmental impacts by 2030 at the regional scale on groundwater‐dependent terrestrial vegetation (GDTV) adapted to various watertable depths, on the basis of the combined consideration of groundwater modelling results and the framework for GDTV risk assessment. The methodology was tested for the historical period from 1984 to 2007, allowing validation of the groundwater model results' applicability to such an assessment. Climate change effects on GDTV were evaluated using nine global climate models under three greenhouse gas emission scenarios by applying the climate projections to groundwater models. It was estimated that under dry climate scenarios, GDTV is likely to be under high and severe risk over more than 20% of its current habitat area. The risk is also likely to be higher under an increase in groundwater abstraction above current volumes. The significance of climate change risk varied across the region, depending on both the intensity of the change in water regime and the sensitivity of the GDTV to such change. Greater effects were projected for terrestrial vegetation dependent on deeper groundwater (6–10 m). Copyright © 2013 John Wiley & Sons, Ltd.